Perayaan Maulid Nabi Muhammad SAW : Membagun Karakter Siswa/I Mas Yaspen Muslim melalui Kegiatan Edukatif - Rani Febriyanni; Nur Halizah; Dea Resti Fauzi Nasution; Riska Ramadhani; Adinda Tri Ramadani; Agustina Agustina; Selly Natasya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to explore the celebration of the Prophet Muhammad's birthday at MAS Yaspend Muslim Pematang Tengah, focusing on its impact on student character development. This research used a qualitative approach with a case study design, involving students, teachers, and the activity organizing committee as research subjects. Data were collected through interviews and direct observation during the celebration activities. The results showed that the celebration of the Prophet's birthday at MAS Yaspend Muslim not only serves as a commemorative event, but also as a means of character building through creative educational activities. The Dai, Cerdas Cermat, Azan, and Sholawat competitions held play an important role in enhancing students' creativity, deepening their understanding of the teachings of the Prophet Muhammad SAW, and internalizing moral and spiritual values such as discipline, cooperation, honesty, and respect. This activity also serves as a medium to address the social challenges of the younger generation, such as drugs and radicalism, by instilling positive values. Overall, the celebration of the Prophet Muhammad's birthday at MAS Yaspend Muslim succeeded in creating a supportive environment for students' character development, equipping them with social and leadership skills, and strengthening spiritual bonds among students. This study suggests that other educational institutions can implement similar activities with more creative and meaningful approaches.